2016
DOI: 10.3329/jname.v13i1.23930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat source and chemical reaction on MHD flow past a vertical plate with variable temperature

Abstract: Abstract:An analysis has been carried out to study the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Similarly the species concentration decreases with time t. It is assumed that the effect of viscous dissipation is negligible and by usual Boussineq's and boundary layer approximation. Based on the above considerations the unsteady flow is governed by the following equations (Rout and Pattanayak [17], Kaprawi [27]):…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly the species concentration decreases with time t. It is assumed that the effect of viscous dissipation is negligible and by usual Boussineq's and boundary layer approximation. Based on the above considerations the unsteady flow is governed by the following equations (Rout and Pattanayak [17], Kaprawi [27]):…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Kumar et al [16] analyzed and reported thermal radiation and mass transfer effects on MHD flow past a vertical oscillating plate with variable temperature effects variable mass diffusion. Rout and Pattanayak [17] examined and reported chemical reaction and radiation effects on MHD flow past an exponentially accelerated vertical porous plate in the presence of heat generation with variable temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [6] studied the influence of variable viscosity and thermal conductivity on laminar MHD free convective boundary layer flow of a dusty fluid past a vertical porous plate with viscous dissipation, Joule heating, and heat generation. Authors in [7] studied the effect of heat source and chemical reaction on MHD flow along a moving vertical plate with variable temperature. Authors in [8] studied a transient MHD free convective flow over a vertical plate with an impulsive motion in presence of heat generation in a rotating system.…”
Section: Introductionmentioning
confidence: 99%
“…Srinivas et al (2014) established the effect of chemical reaction as well as thermal radiation on magnetohydrodynamic flow over an inclined porous extended surface with the consideration of non-uniform heat source/sink: an application to the dynamics of blood flow. Rout et al (2016) studied the consequences of heat generation and chemical reaction on MHD flow past an upright plate with the consideration of variable temperature. Tripath et al (2015) considered and discussed about chemical reaction impact on MHD unforced convective surface over an oscillating vertical plate through porous region.…”
Section: Introductionmentioning
confidence: 99%